I'm going through this "Elementary Differential Equations and Boundary Value Problems" book, by Boyce and DiPrima, and I have a little trouble understanding a passage in the Exact Equations explanation.

"Let $\psi(x,y) = c $ $(1)$ where c is a constant. Assuming that $(1)$ defines $y$ implicitly as a differentiable function of $x$, we can differentiate $(1)$ with respect to x and obtain $\psi_{x}(x,y) + \psi_{y}(x,y)y' = 0$." (ipsis litteris)

How differentiating with respect to $x$ leads up to the second equation exactly? Thanks for any input :)


Let $f(x,z):= \psi(x,z)$, $g(x):=(x,y(x))$ an $h=f\circ g$. Then, from the chain rule $$D h(x)= Df(g(x)) D g(x)=(\psi_x(x,y(x)) \, , \, \psi_y(x,(y(x))^\top (1 \, , \, y'(x)) = \psi_x(x,y(x)) + \psi_y(x,y(x))y'(x)$$ Since $f$ is constant, the derivative of $h$ is $0$, that is, we have $$ \psi_x(x,y(x)) + \psi_y(x,y(x))y'(x) = 0.$$

  • $\begingroup$ Yes, you are right. It should be okay now. $\endgroup$ – Niklas Sep 23 '18 at 14:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.